The Effect of Compensation, Work Environment, Work Motivation on Teacher Turnover Intention at SMK PGRI 4 Surabaya - Prima Nasrul Aziz; Bowo Santoso (Global Economics: International Journal of Economic, Social and Development Sciences, 2024)
This study was conducted to examine the effect of compensation, work environment, and work motivation on teachers' intention to leave in SMK PGRI 4 Surabaya. This research uses quantitative as the method. Using 52 people as respondents and using saturated sampling. The analysis was done using Partial Least Square (PLS). This study found that: 1) Compensation affects teachers' turnover intention, 2) The work environment affects teachers' turnover intention, 3) Work motivation affects teachers' turnover intention.